2020
DOI: 10.1128/mbio.02599-19
|View full text |Cite
|
Sign up to set email alerts
|

The Integrity of the Cell Wall and Its Remodeling during Heterocyst Differentiation Are Regulated by Phylogenetically Conserved Small RNA Yfr1 in Nostoc sp. Strain PCC 7120

Abstract: Yfr1 is a strictly conserved small RNA in cyanobacteria. A bioinformatic prediction to identify possible interactions of Yfr1 with mRNAs was carried out by using the sequences of Yfr1 from several heterocyst-forming strains, including Nostoc sp. strain PCC 7120. The results of the prediction were enriched in genes encoding outer membrane proteins and enzymes related to peptidoglycan biosynthesis and turnover. Heterologous expression assays with Escherichia coli demonstrated direct interactions of Yfr1 with mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…As an alternative strategy to deplete NsiR1 without altering the genomic region upstream of hetF , we have followed a strategy similar to that in Brenes‐Álvarez et al . (2020) and generated a Nostoc strain (OE_as_NsiR1) that constitutively expresses the sequence complementary to nsiR1 . 4 from the trc promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative strategy to deplete NsiR1 without altering the genomic region upstream of hetF , we have followed a strategy similar to that in Brenes‐Álvarez et al . (2020) and generated a Nostoc strain (OE_as_NsiR1) that constitutively expresses the sequence complementary to nsiR1 . 4 from the trc promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…homeostasis and correct cell wall remodeling during heterocysts differentiation [58]. These observations are reminiscent of the competing endogenous RNA (ceRNA) hypothesis in eukaryotic cells, which suggests that competition for a limited pool of regulatory RNAs mediates cross-regulation of mRNAs [61,62].…”
Section: A Set Of Mutually Titrating Pairs Of Srnas Are Conserved Throughout the Cyanobacterial Phylummentioning
confidence: 94%
“…Moreover, in predictions of secondary structures, these likely interacting sequences are located in single-stranded regions. Interaction in vitro has been shown for Yfr1 and Yfr2 from Nostoc 7120 [58].…”
Section: A Set Of Mutually Titrating Pairs Of Srnas Are Conserved Throughout the Cyanobacterial Phylummentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, it is reported that the expression of gene amiC2 is increased due to this small RNA. The overexpression of Yfr1 resulted in a filament broken at connection points between vegetative cells and heterocyst, revealing its role in remodeling in the cell wall during heterocyst differentiation [30].…”
Section: Heterocyst-specific Extracellular Layersmentioning
confidence: 99%